Ideal structure and C^*-algebras of low rank - Brown, Lawrence G.; Pedersen, Gert K. (MATHEMATICA SCANDINAVICA, 2007)
We explore various constructions with ideals in a C^*-algebra A in relation to the notions of real rank, stable rank and extremal richness. In particular we investigate the maximum ideals of low rank. And we investigate the relationship between existence of infinite or properly infinite projections in an extremally rich C^*-algebra and non-existence of ideals or quotients of stable rank one.